Documentary Film in Multitrack Diplomacy: The Case of “Semesta” in Indonesia–European Union Relations - Al Fayzza, Fania Shafira; Putri, Zhaira Najla Salsabila; Simatupang, Helga Yohana (Global Focus, 2026)
ABSTRACT This study examines the practice of multilateral diplomacy within the framework of collaboration between Indonesia and the European Union through the medium of the “Semesta” documentary film. Multitrack diplomacy is positioned as an approach that involves various actors, ranging from states and international organizations to local communities and creative individuals, in building cross-cultural communication and interests. The “Semesta” documentary film case study shows that environmental issues, particularly climate change and local wisdom in natural resource management can serve as a bridge for diplomacy that transcends formal political and economic channels. Through a qualitative analysis of the multitrack diplomacy strategy in Indonesia and European Union collaboration, the study emphasizes the role of film as an instrument of cultural diplomacy that helps strengthen Indonesia's image as a country committed to sustainability. The results of the study show that multitrack diplomacy not only expands the space for interaction between actors but also opens up opportunities for creative collaboration that can represent universal values such as sustainability, solidarity, and global responsibility. Thus, the “Semesta” documentary film is a concrete manifestation of the multitrack diplomacy strategy in strengthening Indonesia-European Union relations through cultural and environmental narratives.